Artificial Intelligence, social networks and artivism. Introduction - Ulloa López, Paola (Nawi, 2026)
Thespeakersatthefourtheditionofthe International Congress of Researchers in Audiovisual Communication and Information Technologies, held in November 2025 at the Faculty of Art, Design, and Audiovisual Communication of our beloved ESPOL, in the city of Guayaquil, have succeeded, with their various contributions, in providing a theoretical approach to certain communicative dynamics that are taking place in today's world. Some of these presentations, transformed into articles, have been collected in this volume of Ñawi. Readers will enjoy works on a variety of topics, such as the tremendous power of social media, which can even lead to the erosion of social ties; the powerful influence of artificial intelligence in the generation of multimedia content; and, from a more critical perspective, artivism that takes a stand against racism.